Politik dan pesantren: Peranan Partai Kebangkitan Bangsa di Lampung, 1999 – 2014 / Chusnunia - Chusnunia, Chusnunia (2017)
National Awakening Party (PKB) is one of the political parties in Indonesia, which was founded by the circle of the Nahdlatul Ulama (NU). The main movement basis of NU is pesantren (traditional Islamic boarding school). Although PKB are originally from Java, however PKB also has strong influence outside of Java, for the instance Lampung. In relation with pesantren, author found three main different perspectives of the pesantren associated with PKB, including pesantren who “open support”, “closed support”, as well as “neutral”. Furthermore the “open support” pesantren will be the main focus in this study. In performing its function as a political party which has strong relation with pesantren, PKB plays different function and role in accordance to the pattern of the support provided by each pesantren. PKB will perform different function and role to the pesanten who shows “open support” and “neutral” pesantren. There are four main functions conducted by PKB as a political party to its counterpart, “open support” pesantren. First is Aggregation function, which very visible especially in the early stage of Indonesian reformation era. Aggregation function is also done by PKB to support the “closed support” or “neutral” pesantren. In conducting the second function, articulation function, PKB confines it into two types of supporting pesantren, whether “open support” or “closed support”. Furthermore, the other two functions, including education and recruitment function are restricted into pesantren who show support, whether “open support” or “closed support”. In conducting the recruitment function, there are distinguish treatment between pesantren who shows “open support” and “closed support”. For pesantren which shows “open support”, PKB will conduct the direct recruitment to member of pesantren and its family. Otherwise for the “closed support” pesantren, PKB only conducts the recruitment to the family. In this study author will derivate two theoretical contributions by Nuemann and Keller. First, according to “theory of functions of political party” by Nuemann, author will show the fact of the function and role of PKB as political party (for the instance in Lampung) as the scope of research. The authors noticed that PKB not only conducts four roles as mentioned by Neumann, but also the conducting the process of spreading the ideology. The function of Political parties is not only recruitment for the new member, but also has to consistently and continuously defend as well as evolve its ideology. Based on the second theory by Keller, in every social group, the existence of ruling group is certainty, including in PKB. Even though, sometime the position of the elite group might be ruling inside or outside the organization structure, however the existence of this group is discernible. In a nutshell, the political party will perform its role and function effectively, if supported by the elite group.